Business Intelligence for the Real-Time Enterprises [electronic resource] : First International Workshop, BIRTE 2006, Seoul, Korea, September 11, 2006, Revised Selected Papers. - BIRTE 2006 (2006 : Seoul, Korea); Bussler, Christoph.; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
PSZJBL